Perancangan Alat Penyiraman Tanaman Otomatis Menggunakan Modul Wifi Esp8266 - Mei Safrina; Linna Oktaviana Sari; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Currently, technological advances are in line with advances in science, so there are many variations that are created for the benefit of human life. Therefore, many problems can be solved by utilizing modern technology, one of which is in agriculture. Watering plants is still mostly done manually and people have difficulty maintaining these plants. Due to the busyness of people's work, it’s difficult to divide the time which makes the plants uncontrollable, so that the plants aren’t well maintained. Utilization of IoT makes daily work easier, especially technology that is practical and efficient. IoT makes devices able to communicate such as sending and receiving data. For this reason, the design and manufacture of an Internet of Things (IoT)-based automatic plant watering control device is carried out. This study designed an automatic watering device consisting of ESP8266, soil moisture sensor and DHT11, where the working system of this tool includes automatic watering of plants based on the water content in the soil, and notifications will be sent to the telegram application. The design of this system will be divided into into three stages, namely, hardware design, software, and use case diagrams. Based on the design results, this automatic plant watering device works successfully by detecting room temperature and reading soil moisture levels. With this tool, it’s hoped that plant owners will get data and values for controlling soil temperature and humidity in accordance with leek plants and become an alternative solution for plant owners in maintaining their plants. The system designed has been able to monitor plant watering, as well as send notifications to users in the form of information about the state of room temperature and soil moisture in plants through the telegram application.Keywords : Internet of Things, Soil Moisture Sensor, DHT11. Telegram